Synthesis and Biological Evaluation of Perylene Derivatives as Telomerase Inhibitors in Human ProstateCancer Cells - Ratasark Summart (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Telomerase inhibition is proposed as a new strategy to treat cancer and prevent relapse of cancer and metastasis, with a promise of lesser toxicity to normal cells. Telomerase inhibitors are suggested to be the ideal class of drugs for patients diagnosed with benign cancer, and patients who are in cancer remission to prevent cancer relapse. Perylene derivatives have been studied as G-quadruplex ligands that inhibit telomerase by facilitating G-quadruplex formation at the 3-end of telomeric DNA, preventing the access of telomerase to its substrate. PIPER, the prototypic perylene derivative, has been shown to reduce telomerase activity in lung and prostate cancer cells, leading to telomere shortening and cellular senescence of these cancer cells. However, PIPER has a problem of hydrosolubility and the propensity to aggregate. In this study, we designed and synthesized a new asymmetric perylene diimide, aPDI-PHis, which has the same ethyl-piperidine group as PIPER on one sidechain, and histidine on another sidechain. We hypothesized that this compound would have a better hydrosolubility at the physiological relevant pHs but still possess G-quadruplex selectivity and telomerase inhibition. New perylene derivatives, including symmetric perylene diimide and asymmetric perylene diimide derivatives were synthesized and characterized. Their solubility and absorption spectra were studied. DNA binding selectivity of these compounds with various G-quadruplex motifs and duplex DNA was investigated using spectrophotometry, fluorescent intercalator displacement (FID) assay, and duplex-quadruplex competition. Results showed that aPDI-PHis, an asymmetric perylene diimide derivative, had a broader range of solubility than PIPER, the prototypic perylene diimide derivative. It also bound better to G-quadruplex and had better telomerase inhibition than PIPER. The results from studies of perylene derivatives in prostate cancer cells confirmed that these compounds could suppress hTERT expression as well as telomerase activity in PC3 and LNCaP cells. These results suggest that having two different sidechains with selective properties might enhance the activity of perylene derivatives, which might lead to a better drug to use as a telomerase inhibitor.